2021
DOI: 10.2298/sarh210103082d
|View full text |Cite
|
Sign up to set email alerts
|

The role of interleukin-4 and interleukin-5 Th2 cytokines in assessing severity and prognosis of acute pancreatitis

Abstract: Introduction/Objective. Acute pancreatitis (AP) is relatively common disease which in most patients has favorable course. However, in approximately 20% patients, the course of the disease is more severe with high mortality (40-50%). The evaluation of disease severity is now primarily based on protocols that includes clinical, laboratory, and radiographic diagnostic procedures, APACHE II score, Ranson score, CT index, and CT necrosis score. Key cells in the immunopathogenesis of AP are T-lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In patients with SAP complicated by necrosis and/or sepsis, these levels continued to increase throughout the seventh day. Furthermore, it was found that the levels of IL-5 and IL-4 could serve as early indicators of the severity of AP, as well as early markers of sepsis and overall prognosis, given their significant statistical correlation with outcomes, the presence of SIRS and the Ranson score [ 29 ].…”
Section: Interleukins 4 and 5 (Il-4 And Il-5)mentioning
confidence: 99%
“…In patients with SAP complicated by necrosis and/or sepsis, these levels continued to increase throughout the seventh day. Furthermore, it was found that the levels of IL-5 and IL-4 could serve as early indicators of the severity of AP, as well as early markers of sepsis and overall prognosis, given their significant statistical correlation with outcomes, the presence of SIRS and the Ranson score [ 29 ].…”
Section: Interleukins 4 and 5 (Il-4 And Il-5)mentioning
confidence: 99%